Challenges in Perioperative management of spontaneous acute subdural hematoma in haemophilia patients - Gautam, Sachidanand; Singhal, Manoj; Panchariya, Piyush Kumar; Acharya, Jigmisha (Nepal Journal of Neuroscience, 2022)
Intracranial hemorrhage in patients with hemophilia is associated with high mortality and morbidity. We report a case of 15 years old boy with haemophilia A, who presented with a spontaneous acute subdural hematoma and underwent craniotomy for clot evacuation. The patient also received Factor VIII infusions peri-operatively along with other measures, to decrease blood loss.The patient presented with signs of raised intracranial pressure and received mannitol intra-operatively and postoperatively to prevent brain edema. Hypertonic saline (3 ml/kg of 3% solution) was also given over 30 minutes for brain relaxation. Recommendations for peri-operative preparation and management of haemophilia, especially in the setting of emergency major surgery were also reviewed.